Medicine ball workouts : strengthen major and supporting muscle groups for increased power, coordination, and core stability - Stewart, Brett, ....- (Berkeley : Ulysses Press, 2013)
SUPER-CHARGE YOUR WORKOUT WITH A MEDICINE BALL Tap the power of the weighted medicine ball to tone your whole body and build lean muscles and a shredded core. Medicine Ball Workouts shows how to use one of the most useful and versatile fitness tools out there to curl, press, toss and catch your way to getting in the best shape of your life. Perfect for beginners and advanced athletes alike, this book details medicine-ball exercises like: PUSH-UPS for increased upper-body & core strength SQUATS, LUNGES & THRUSTERS to build a strong powerful lower body BURPEES & TOSSES to improve explosive speed & full-body power TURKISH GET-UPS to develop flexibility & dexterity With day-by-day programs and easy-to-follow, step-by-step exercises, Medicine Ball Workouts transforms simple moves into fun, challenging and highly effective functional cross-training workouts for total-body fitness and a ripped physique. heart-pounding cardio workouts that tone the body from shoulders to toes.
Keywords: Krachttraining